1990
DOI: 10.1364/ao.29.002913
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Raman spectroscopy from reacting optically levitated microdroplets

Abstract: Time-resolved Raman spectroscopy is evaluated as a tool for studying reactions in aerosol microdroplets. As a test reaction, the absorption of D(2)O vapor by an optically levitated glycerol droplet is considered. With the present apparatus, time scales of the order of 1 s have been resolved. By considering the relative amplitude of various features, the composition of the suspended droplet can be estimated as a function of time. In addition, for the D(2)O-glycerol system the average temperature of the opticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…l v l 6 . 2 5 --2 8 C arls et al 29 observed the absorption of D 2 0 vapour by an optically levitated glycerol droplet. However, their spectra did not show any structural resonances.…”
Section: Introductionmentioning
confidence: 98%
“…l v l 6 . 2 5 --2 8 C arls et al 29 observed the absorption of D 2 0 vapour by an optically levitated glycerol droplet. However, their spectra did not show any structural resonances.…”
Section: Introductionmentioning
confidence: 98%
“…[233] Though no cavity-enhancement is needed for large droplets for this scheme, cavityenhancement could potentially enable pH-determination in sub-micron droplets. [231] Cavityenhanced Raman scattering can then be used to probe chemical composition of the aerosols, [234] including ionic strength, [231] critical parameters for environmental or atmospheric models, and even how the composition of a single droplet changes over time [235] or allow visualization of a phasetranstiion. [236] The high circulating powers due to the cavity-enhancement lend the technique particularly well to non-linear Raman processes.…”
Section: Spectroscopymentioning
confidence: 99%
“…In a pioneer work on Raman scattering applied to droplets, Carls et al (1990) investigated the chemical absorption of D 2 O vapor by an acoustically levitated droplet of glycerol (diameter 25 lm). Although the chemical evolution of the droplet could be clearly observed on the Raman spectra, quantitative interpretation remained difficult due to MDR peaks.…”
Section: Spontaneous Raman Scatteringmentioning
confidence: 99%